Effect of Nanoparticles Concentration on Zinc Oxide-Iron (III) Oxide Hybrid Nanofluid for Enhanced Oil Recovery - Zulkiflee, Nurul Nabilah Husna (2018)
The use of nanomaterials for enhanced oil recovery (EOR) has shown both constructive and negative results in previous studies. This is because different nanoparticles exhibit different properties and thus favour differently in oil recovery. In this study, ZnO nanoparticles were dispersed with Fe3O4 nanoparticles in brine to formulate a ZnO-Fe3O4 hybrid nanofluid at concentration of 0.05 wt %. In this paper, five nanofluids were prepared each with respective nanofluid formulation (ZnO: Fe3O4); 0%:100%, 30%:70%, 50%:50%, 70%:30% and 100%:0%. Characterization of nanofluids were done by testing the viscosity against increasing temperature and shear rate, measuring the density and Zeta potential of each nanofluid formulation, interfacial tension (IFT) between crude oil and respective nanofluid as well as wettability alteration by the nanofluid. By introducing ZnO and/or Fe3O4 nanoparticles to brine, viscosity of the nanofluids were increased and IFT was also reduced significantly. The viscosity recorded was higher than viscosity of crude oil and brine. Thus, favouring oil mobility out of the reservoir. Lowest IFT was recorded at ~12.0 mN/m with a total reduction of ~9 mN/m prior to nanoparticles addition to brine. Besides, the formulated nanofluids were also able to alter wettability of oil-wet synthetic silica plate to water-wet which was measured through recording the reduction of contact angle measurement over stipulated period of time. However, unsatisfactory Zeta potential was shown proving that the colloidal suspension were unstable and nanoparticles aggregation occurred. It was also discovered that pH has an influence on Zeta potential and mitigation measures shall be taken to tune the pH of nanofluids further apart from the isoelectric point (IEP) which is the point where the Zeta potential of nanoparticles is 0 mV. Greatly charged surface of nanoparticles is highly desirable to promote repulsive force among neighbouring nanoparticles. To conclude the study, performance of each nanofluid with respect to each characterization step was then compared to that of brine as the benchmark and an evaluation was done using weighted score matrix evaluation method to ultimately determine the optimum nanofluid formulation that could favour EOR.